PHYTOTOXICITY AND GROWTH OF COFFEE PLANTS AS A FUNCTION OF THE APPLICATION OF HERBICIDE 2,4-D - Voltolini, Giovani Belutti; Castanheira, Dalyse Toledo; da Silva, Larissa Cocato; Alecrim, Ademilson de Oliveira; Rezende, Tiago Teruel; Barbosa, João Paulo Rodrigues Alves Delfino; Guimarães, Rubens José (Coffee Science - ISSN 1984-3909, 2019)
Weed control in coffee is of great importance for there is a great interference, standing out the competition for water, light and nutrients. Among the control methods, chemical control is highlighted as a function of its efficiency. However, the incorrect application of herbicides may imply the occurrence of drift, resulting in damage to coffee development due to phytotoxicity. In this context, the objective of this study was to evaluate the symptoms and phytotoxicity effects caused by the herbicide 2,4-D drift on the morphological, physiological and anatomical characteristics of coffee seedlings. The experiment was carried out in a greenhouse with ‘Topázio MG1190’ coffee seedlings (Coffea arabica L.), planted in 11-L pots. A randomized block design with four treatments and four replicates was used. The treatments were: 0%; 10%; 25% and 50% of the recommended commercial dose of 2,4-D (2.5 L.ha-1). Each plot consisted of three plants. The evaluations were performed at 74 days after implantation. Morphological, physiological, anatomical and phytotoxicity symptoms were evaluated as a function of the simulated herbicide drift. Coffee seedlings intoxicated by the herbicide 2,4-D presented hyponastic, chlorosis, shriveling and leaf anomalies. In the orthotropic branch, bending was observed in its extension, besides thickening in the collar region; in the plagiotropic branch, cracking was observed. Herbicide drift negatively affects the development of coffee plants. The coffee physiology was affected as a function of herbicide drift, but without damage to the leaf anatomy.